Collaborative studies on in vitro digestibility of dietary proteins based on the INFOGEST Quant protocol: toward international standardization - Lotti Egger; Ana Blanco-Doval; Cédric Brügger; Raquel Sousa; Lychou Abbühl; Marta Santos Hernández; Beatriz Miralles; Cristina Gómez-Marin; Adam Macierzanka; Patrycja Szumała; Ilona E. Kłosowska-Chomiczewska; Ana Isabel Mulet-Cabero; et al. (Food Research International, 2026)

How Robust Are Genomic Offset Predictions to Methodological Choices? Insights From Perennial Ryegrass - Marie Pegard; Susanne Lachmuth; Jean‐Paul Sampoux; José Blanco‐Pastor; Philippe Barre; Matthew C. Fitzpatrick (Molecular Ecology, 2026)
Genomic offsets are increasingly used to quantify the mismatch between a population's current genetic composition and the composition predicted under changed environmental conditions. While genomic offset is a promising tool for assessing climate maladaptation, the sensitivity of predictions to different methodological choices is not well understood. In this study, we compared two fundamentally different approaches to detect outliers before predicting genomic offsets: Gradient Forest (GF, non‐linear, non‐parametric) and Canonical Correlation Analysis (CANCOR, linear, parametric). To do so, we used 457 natural populations of perennial ryegrass ( Lolium perenne L.), an important agricultural forage species throughout Europe. Using a data set of 189,968 SNPs and 75 climatic variables, we experimentally validated genomic offsets against 105 phenotypic traits measured across three common gardens during multiple years. We also assessed the sensitivity of outlier detection and genomic offset predictions to the number and spatial distribution of sampled populations. Both GF and CANCOR detected a substantial number of outlier loci associated with environmental gradients (2113 and 653, respectively), with 429 loci identified by both approaches. When used to model spatial variation in genetic adaptation and estimate genomic offsets, the different outlier sets produce spatially congruent projections. We also found significant correlations between experienced genomic offset in the common garden predicted by both outlier sets and phenotypic traits, identifying traits that could serve as good fitness proxies for assessing climate risk. Analyses based on different population subsamples revealed that GF was less sensitive to sample size and geographic biases than CANCOR. Our findings provide practical guidance for designing genomic offset studies in both agricultural and natural systems and suggest that non‐linear, non‐parametric methods like GF may be less sensitive to sampling design and therefore potentially more robust for predicting climate maladaptation.

Rat and human primary proximal tubule epithelial cells allow for cross-species comparisons of drug-induced nephrotoxicity in vitro - Stan A. Zuidervaart; Bobin G. Abraham; Paul A. Fitzpatrick; Anna-Karin Sjögren; Catherine C. Bell (Archives of Toxicology, 2026)

Spatial differences in the ovine cervical microenvironment at the follicular and luteal phases of the oestrous cycle; Implications for sperm transport - N. Johnston; E. Bini; E. Fitzpatrick; C. Reid; S. Fair (Theriogenology, 2026)

Assessment of Fellowship Didactic Curricula in Hematology/Oncology: Cross-Sectional Findings From the PODCAST-HOF Trial - Ronak H. Mistry; Karine Tawagi; Daniel J. Hausrath; Samantha A. Armstrong; Inas A. Abuali; Ankoor N. Biswas; Srijan Valasapalli; Pranali S. Pachika; Moriah K. Forster; Ericson Stoen; Yurhee Lee; Giuliana G. Berardi; et al. (Journal of Cancer Education, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Composition, Growth, Succession, and Function in the Cladophora Microbiome: Insights From Quantitative Stable Isotope Probing and NanoSIMS Imaging - Raina M. Fitzpatrick; Bruce A. Hungate; Mary Power; Megan Foley; Ty Samo; Egbert Schwartz; Micheala Hayer; Peter K. Weber; Jennifer Pett‐Ridge; Jane C. Marks (Environmental Microbiology, 2025)
The branching green macroalga Cladophora glomerata and its epiphytic microbiome dominate summer biomass in the Eel River, a Northern California river under Mediterranean (summer drought, winter rain) seasonality. Green Cladophora streamers proliferate in early summer, then change to yellow and then red‐brown as epiphyte loads increase. We characterised successional changes in epiphytic bacteria on Cladophora , examining both community composition and growth rates, using quantitative Stable Isotope Probing (qSIP) and 16S rRNA gene amplicon sequencing. The number of bacterial taxa increased with succession while growth rates peaked in the middle stage. NanoSIMS imaging confirmed high sulphur (S) concentrations in Cladophora cell walls relative to surrounding biomass, coinciding with a bloom of sulphur bacteria (bacteria that reduce or oxidise sulphur/sulphates). In general, relative abundances and growth rates were independent, indicating that either metric alone is insufficient for understanding how taxonomy and functional groups affect ecosystem processes. For instance, the relative abundance of nitrogen fixers peaked in the late summer when their relative growth rates were slowest. Such patterns may be driven by space competition limiting growth. Together, changes in abundance and relative growth rates suggest different limiting factors for different functional groups in the Cladophora microbiome at multiple successional stages.

Harvest legacies and climate change interact to shape forest structure and biomass through time - Lucien Fitzpatrick; Bailey A. Murphy; Meghan G. Midgley; Ankur R. Desai; Michael C. Dietze; Kurt Dreisilker; Christine R. Rollinson (Journal of Environmental Management, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Proteomic Analysis of Chronic Binge Alcohol-Induced Hippocampal and Anterior Cingulate Cortex Neuroadaptations in Simian Immunodeficiency Virus (SIV)-Infected Female Rhesus Macaques - Taylor Fitzpatrick-Schmidt; Amirsalar Mansouri; Jiri Adamec; Jennifer Klein; Larry Coleman; Kimberly N. Edwards; Liz Simon; Patricia E. Molina; Michael C. Salling; Scott Edwards (Journal of Neuroimmune Pharmacology, 2025)

Inpatient referrals to a specialist falls and syncope service: prevalence of STOPPFall FRIDs and review of deprescribing patterns - D. O’Donnell; T. Zainal; K. Malomo; N. Fitzpatrick; C. Rice; L. Byrne; R. Briggs; C. Cunningham; R. A. Kenny; A. H. Lavan (European Journal of Clinical Pharmacology, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Species identification of modern and archaeological shark and ray skeletal tissues using collagen peptide mass fingerprinting - Michael Buckley; Ellie-May Oldfield; Cristina Oliveira; Clara Boulanger; Andrew C. Kitchener; Nicole R. Fuller; Traci Ardren; Victor D. Thompson; Scott M. Fitzpatrick; Michelle J. LeFebvre (Frontiers in Marine Science, 2024)
Introduction Elasmobranchs, such as sharks and rays, are among the world’s most endangered vertebrates, with over 70% loss in abundance over the past 50 years due to human impacts. Zooarchaeological baselines of elasmobranch diversity, distribution, and exploitation hold great promise for contributing essential historical contexts in the assessment of contemporary patterns in their taxonomic diversity and vulnerability to human-caused extinction. Yet, the historical ecology of elasmobranchs receives relatively less archaeological attention compared to that of ray-finned fishes or marine mammals, largely due to issues of taxonomic resolution across zooarchaeological identifications. Methods We explore the use of Zooarchaeology by Mass Spectrometry (ZooMS) for species identification in this unstudied group, using an archaeological case study from the marine environments of the Florida Keys, a marine biodiversity hotspot that is home to an array of elasmobranch species and conservation efforts. By comparison with 39 modern reference species, we could distinguish 12 taxa within the zooarchaeological assemblage from the Clupper archaeological site (Upper Matecumbe Key) that included nine sharks, two rays and a sawfish. Results and discussion The results indicate that, through additional complexity of the collagen peptide mass fingerprint, obtained due to the presence of the cartilaginous type II collagen, ZooMS collagen peptide mass fingerprinting provides exceptionally high taxonomic resolution in this group, yielding species-level identifications in all cases where sufficient reference material was used. This case study also highlights the added value of ZooMS for taxa that are more difficult to distinguish in zooarchaeological analyses, such as vertebrae of the Atlantic sharpnose shark ( Rhizoprionodon terraenovae ) and the hammerhead sharks ( Sphyrna spp.) in the Florida Keys. Therefore, the application of collagen peptide mass fingerprinting to elasmobranchs offers great potential to improve our understanding of their archaeological past and historical ecology.

Strengths and limitations of the worm development and activity test (wDAT) as a chemical screening tool for developmental hazards - Piper Reid Hunt; Bonnie Welch; Jessica Camacho; Joelle K. Salazar; Megan L. Fay; Jon Hamm; Patricia Ceger; Dave Allen; Suzanne C. Fitzpatrick; Jeffrey Yourick; Robert L. Sprando (Toxicology and Applied Pharmacology, 2024)

P07-09 Spatio-temporal multi-omics analysis of lung tissue and matched biofluids identifies circulatory safety biomarkers for monitoring inhaled drug induced lung injury - M.M. Majumder; E. Williams; M.O. Lindvall; A. Jarnuczak; G. Hamm; C. Di Poto; A.A. Iannetta; J.L. Touza; E.L. Allman; E. Miele; J. Lindgren; E. Sand; et al. (Toxicology Letters, 2024)

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Genetic structure of restored Brook Trout populations in the Southern Appalachian Mountains indicates successful reintroductions - Rebecca J. Smith; David C. Kazyak; Matt A. Kulp; Barbara A. Lubinski; Benjamin M. Fitzpatrick (Conservation Genetics, 2024)

Mechanistic safety assessment via multi-omic characterisation of systemic pathway perturbations following in vivo MAT2A inhibition - Valentina Fogal; Filippos Michopoulos; Andrew F. Jarnuczak; Ghaith M. Hamza; Stephanie Harlfinger; Paul Davey; Heather Hulme; Stephen J. Atkinson; Piotr Gabrowski; Tony Cheung; Michael Grondine; Clare Hoover; et al. (Archives of Toxicology, 2024)
The tumour suppressor p16/CDKN2A and the metabolic gene, methyl-thio-adenosine phosphorylase (MTAP), are frequently co-deleted in some of the most aggressive and currently untreatable cancers. Cells with MTAP deletion are vulnerable to inhibition of the metabolic enzyme, methionine-adenosyl transferase 2A (MAT2A), and the protein arginine methyl transferase (PRMT5). This synthetic lethality has paved the way for the rapid development of drugs targeting the MAT2A/PRMT5 axis. MAT2A and its liver- and pancreas-specific isoform, MAT1A, generate the universal methyl donor S-adenosylmethionine (SAM) from ATP and methionine. Given the pleiotropic role SAM plays in methylation of diverse substrates, characterising the extent of SAM depletion and downstream perturbations following MAT2A/MAT1A inhibition (MATi) is critical for safety assessment. We have assessed in vivo target engagement and the resultant systemic phenotype using multi-omic tools to characterise response to a MAT2A inhibitor (AZ’9567). We observed significant SAM depletion and extensive methionine accumulation in the plasma, liver, brain and heart of treated rats, providing the first assessment of both global SAM depletion and evidence of hepatic MAT1A target engagement. An integrative analysis of multi-omic data from liver tissue identified broad perturbations in pathways covering one-carbon metabolism, trans-sulfuration and lipid metabolism. We infer that these pathway-wide perturbations represent adaptive responses to SAM depletion and confer a risk of oxidative stress, hepatic steatosis and an associated disturbance in plasma and cellular lipid homeostasis. The alterations also explain the dramatic increase in plasma and tissue methionine, which could be used as a safety and PD biomarker going forward to the clinic.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Genomic insights into hybrid zone formation: The role of climate, landscape, and demography in the emergence of a novel hybrid lineage - Constance E. Bolte; Tommy Phannareth; Michelle Zavala‐Paez; Brianna N. Sutara; Muhammed F. Can; Matthew C. Fitzpatrick; Jason A. Holliday; Stephen R. Keller; Jill A. Hamilton (Molecular Ecology, 2024)
Population demographic changes, alongside landscape, geographic and climate heterogeneity, can influence the timing, stability and extent of introgression where species hybridise. Thus, quantifying interactions across diverged lineages, and the relative contributions of interspecific genetic exchange and selection to divergence at the genome‐wide level is needed to better understand the drivers of hybrid zone formation and maintenance. We used seven latitudinally arrayed transects to quantify the contributions of climate, geography and landscape features to broad patterns of genetic structure across the hybrid zone of Populus trichocarpa and P. balsamifera and evaluated the demographic context of hybridisation over time. We found genetic structure differed among the seven transects. While ancestry was structured by climate, landscape features influenced gene flow dynamics. Demographic models indicated a secondary contact event may have influenced contemporary hybrid zone formation with the origin of a putative hybrid lineage that inhabits regions with higher aridity than either of the ancestral groups. Phylogenetic relationships based on chloroplast genomes support the origin of this hybrid lineage inferred from demographic models based on the nuclear data. Our results point towards the importance of climate and landscape patterns in structuring the contact zones between P. trichocarpa and P. balsamifera and emphasise the value whole genome sequencing can have to advancing our understanding of how neutral processes influence divergence across space and time.

The companion dog as a model for inflammaging: a cross-sectional pilot study - Sarah M. Schmid; Jessica M. Hoffman; Jena Prescott; Holley Ernst; Daniel E. L. Promislow; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; et al. (GeroScience, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Equivalent roles of marine subsidies and island characteristics in shaping island bird communities - Debora S. Obrist; Patrick J. Hanly; Jeremiah C. Kennedy; Owen T. Fitzpatrick; Sara B. Wickham; Wiebe Nijland; Luba Y. Reshitnyk; Chris T. Darimont; Brian M. Starzomski; John D. Reynolds (Journal of Biogeography, 2024)
Aim Species distributions across islands are shaped by dispersal limitations, environmental filters and biotic interactions but the relative influence of each of these processes has rarely been assessed. Here, we examine the relative contributions of island characteristics, marine subsidies, species traits, and species interactions on avian community composition. Location Central Coast region of British Columbia, Canada. Taxon Terrestrial breeding birds. Methods We observed 3610 individuals of 32 bird species on 89 islands that spanned multiple orders of magnitude in area (0.0002–3 km 2 ). We fit a spatially explicit joint species distribution model to estimate the relative contributions of island physical characteristics, island‐specific inputs of marine subsidies, species' traits, and biotic interactions on species distributions. Biogeographic characteristics included island area, isolation, and habitat heterogeneity, while marine influence was represented by forest‐edge soil δ 15 N, wrack biomass, shoreline substrate, and distance to shore. This approach also allowed us to estimate how much variation in distributions resulted from species' biological traits (i.e. body mass, feeding guild, feeding height, and nesting height). Results Bird species distributions were determined almost equivalently by island biogeographic characteristics (23.5% of variation explained) and marine influence (24.8%). We detected variation in species‐specific responses to both island biogeographic characteristics and marine influence, but no significant effect of any biological trait examined. Additionally, we found evidence that habitat preferences were a more important driver than competitive interactions. Main Conclusions Although most island biogeographic studies focus only on islands' physical characteristics, we found evidence for an equivalent role of marine subsidy in structuring island bird communities. Our study suggests that for small islands, disentangling the effects of island biogeographic characteristics, marine inputs, and biotic interactions is a useful next step in understanding species distributions.

Retrospective analysis of dog study data from food and color additive petitions - Brenna M. Flannery; Alexandra E. Turley; Njwen Anyangwe; Antonia Mattia; Catherine Whiteside; Steven Hermansky; Heather R. Schaefer; Tina Tyler; Suzanne C. Fitzpatrick (Regulatory Toxicology and Pharmacology, 2023)

Parallel evaluation of alternative skin barrier models and excised human skin for dermal absorption studies in vitro - Alec T. Salminen; Kelly J. Davis; Robert P. Felton; Nathania Nischal; Linda S. VonTungeln; Frederick A. Beland; Kristy Derr; Paul C. Brown; Marc Ferrer; Linda M. Katz; Nicole C. Kleinstreuer; Jonathan Leshin; et al. (Toxicology in Vitro, 2023)

Development of an Interprofessional Small Bowel Placement Training Program - A. Fitzpatrick; M. Houser; C. Fackler; A. Patton; K. Roberts (Journal of the Academy of Nutrition and Dietetics, 2023)

Using aerial LiDAR to assess regional availability of potential habitat for a conservation dependent forest bird - Darin J. McNeil; G. Fisher; Cameron J. Fiss; Andrew J. Elmore; Matthew C. Fitzpatrick; Jeff W. Atkins; Jonathan Cohen; Jeffery L. Larkin (Forest Ecology and Management, 2023)

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Banking on a new understanding: translational opportunities from veterinary biobanks - D. LaLonde-Paul; L. Mouttham; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; Virginia R. Fajt; Annette L. Fitzpatrick; Unity Jeffery; et al. (GeroScience, 2023)

On the application of rainfall projections from a convection-permitting climate model to lumped catchment models - M.J. Ascott; V. Christelis; D.J. Lapworth; D.M.J. Macdonald; C. Tindimugaya; A. Iragena; D. Finney; R. Fitzpatrick; J.H. Marsham; D.P. Rowell (Journal of Hydrology, 2023)

Once-daily feeding is associated with better health in companion dogs: results from the Dog Aging Project - Emily E. Bray; Zihan Zheng; M. Katherine Tolbert; Brianah M. McCoy; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; et al. (GeroScience, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A working guide to harnessing generalized dissimilarity modelling for biodiversity analysis and conservation assessment - Karel Mokany; Chris Ware; Skipton N. C. Woolley; Simon Ferrier; Matthew C. Fitzpatrick (Global Ecology and Biogeography, 2022)
Aim Generalized dissimilarity modelling (GDM) is a powerful and unique method for characterizing and predicting beta diversity, the change in biodiversity over space, time and environmental gradients. The number of studies applying GDM is expanding, with increasing recognition of its value in improving our understanding of the drivers of biodiversity patterns and in implementing a wide variety of spatial assessments relevant to biodiversity conservation. However, apart from the original presentation of the GDM technique, there has been little guidance available to users on applying GDM to different situations or on the key modelling decisions required. Innovation We present an accessible working guide to GDM. We describe the context for the development of GDM, present a simple statistical explanation of how model fitting works, and step through key considerations involved in data preparation, model fitting, refinement and assessment. We then describe how several novel spatial biodiversity analyses can be implemented using GDM, with code to support broader implementation. We conclude by providing an overview of the range of GDM‐based analyses that have been undertaken to date and identify priority areas for future research and development. Main conclusions Our vision is that this working guide will facilitate greater and more rigorous use of GDM as a powerful tool for undertaking biodiversity analyses and assessments.

Reproductive benefits associated with dispersal in headwater populations of Trinidadian guppies ( Poecilia reticulata ) - Isabela L. Borges; Jillian C. Dangerfield; Lisa M. Angeloni; W. Chris Funk; Sarah W. Fitzpatrick (Ecology Letters, 2022)
Theory suggests that the evolution of dispersal is balanced by its fitness costs and benefits, yet empirical evidence is sparse due to the difficulties of measuring dispersal and fitness in natural populations. Here, we use spatially explicit data from a multi‐generational capture–mark–recapture study of two populations of Trinidadian guppies ( Poecilia reticulata ) along with pedigrees to test whether there are fitness benefits correlated with dispersal. Combining these ecological and molecular data sets allows us to directly measure the relationship between movement and reproduction. Individual dispersal was measured as the total distance moved by a fish during its lifetime. We analysed the effects of dispersal propensity and distance on a variety of reproductive metrics. We found that number of mates and number of offspring were positively correlated to dispersal, especially for males. Our results also reveal individual and environmental variation in dispersal, with sex, size, season, and stream acting as determining factors.

Advancing Social Equity in and Through Marine Conservation - Nathan J. Bennett; Laure Katz; Whitney Yadao-Evans; Gabby N. Ahmadia; Scott Atkinson; Natalie C. Ban; Neil M. Dawson; Asha de Vos; Juno Fitzpatrick; David Gill; Mael Imirizaldu; Naia Lewis; et al. (Frontiers in Marine Science, 2021)
Substantial efforts and investments are being made to increase the scale and improve the effectiveness of marine conservation globally. Though it is mandated by international law and central to conservation policy, less attention has been given to how to operationalize social equity in and through the pursuit of marine conservation. In this article, we aim to bring greater attention to this topic through reviewing how social equity can be better integrated in marine conservation policy and practice. Advancing social equity in marine conservation requires directing attention to: recognition through acknowledgment and respect for diverse peoples and perspectives; fair distribution of impacts through maximizing benefits and minimizing burdens; procedures through fostering participation in decision-making and good governance; management through championing and supporting local involvement and leadership; the environment through ensuring the efficacy of conservation actions and adequacy of management to ensure benefits to nature and people; and the structural barriers to and institutional roots of inequity in conservation. We then discuss the role of various conservation organizations in advancing social equity in marine conservation and identify the capacities these organizations need to build. We urge the marine conservation community, including governments, non-governmental organizations and donors, to commit to the pursuit of socially equitable conservation.

Can indicator species guide conservation investments to restore connectivity in Great Lakes tributaries? - Kimberly B. Fitzpatrick; Allison T. Moody; Austin Milt; Matthew E. Herbert; Mary Khoury; Eugene Yacobson; Jared A. Ross; Patrick J. Doran; Michael C. Ferris; Peter B. McIntyre; Thomas M. Neeson (Biodiversity and Conservation, 2021)

Contemporary range position predicts the range‐wide pattern of genetic diversity in balsam poplar ( Populus balsamifera L.) - Andrew V. Gougherty; Vikram E. Chhatre; Stephen R. Keller; Matthew C. Fitzpatrick (Journal of Biogeography, 2020)
Aim Patterns of genetic diversity within species’ ranges can reveal important insights into effects of past climate on species’ biogeography and current population dynamics. While numerous biogeographic hypotheses have been proposed to explain patterns of genetic diversity within species’ ranges, formal comparisons and rigorous statistical tests of these hypotheses remain rare. Here, we compared seven hypotheses for their abilities to describe the geographic pattern of two metrics of genetic diversity in balsam poplar ( Populus balsamifera ), a northern North American tree species. Location North America. Taxon Balsam poplar ( Populus balsamifera L.). Methods We compared seven hypotheses, representing effects of past climate and current range position, for their ability to describe the geographic pattern of expected heterozygosity and per cent polymorphic loci across 85 populations of balsam poplar. We tested each hypothesis using spatial and non‐spatial least‐squares regression to assess the importance of spatial autocorrelation on model performance. Results We found that both expected heterozygosity and per cent polymorphic loci could best be explained by the current range position and genetic structure of populations within the contemporary range. Genetic diversity showed a clear gradient of being highest near the geographic and climatic range centre and lowest near range edges. Hypotheses accounting for the effects of past climate (e.g. past climatic suitability, distance from the southern edge), in contrast, had comparatively little support. Model ranks were similar among spatial and non‐spatial models, but residuals of all non‐spatial models were significantly autocorrelated, violating the assumption of independence in least‐squares regression. Main conclusions Our work adds strong support for the “Central‐Periphery Hypothesis” as providing a predictive framework for understanding the forces structuring genetic diversity across species’ ranges, and illustrates the value of applying a robust comparative model selection framework and accounting for spatial autocorrelation when comparing biogeographic models of genetic diversity.

Delineation of phenotypes and genotypes related to cohesin structural protein RAD21 - Lianne C. Krab; Iñigo Marcos-Alcalde; Melissa Assaf; Meena Balasubramanian; Janne Bayer Andersen; Anne-Marie Bisgaard; David R. Fitzpatrick; Sanna Gudmundsson; Sylvia A. Huisman; Tugba Kalayci; Saskia M. Maas; Francisco Martinez; et al. (Human Genetics, 2020)
RAD21 encodes a key component of the cohesin complex, and variants in RAD21 have been associated with Cornelia de Lange Syndrome (CdLS). Limited information on phenotypes attributable to RAD21 variants and genotype–phenotype relationships is currently published. We gathered a series of 49 individuals from 33 families with RAD21 alterations [24 different intragenic sequence variants (2 recurrent), 7 unique microdeletions], including 24 hitherto unpublished cases. We evaluated consequences of 12 intragenic variants by protein modelling and molecular dynamic studies. Full clinical information was available for 29 individuals. Their phenotype is an attenuated CdLS phenotype compared to that caused by variants in NIPBL or SMC1A for facial morphology, limb anomalies, and especially for cognition and behavior. In the 20 individuals with limited clinical information, additional phenotypes include Mungan syndrome (in patients with biallelic variants) and holoprosencephaly, with or without CdLS characteristics. We describe several additional cases with phenotypes including sclerocornea, in which involvement of the RAD21 variant is uncertain. Variants were frequently familial, and genotype–phenotype analyses demonstrated striking interfamilial and intrafamilial variability. Careful phenotyping is essential in interpreting consequences of RAD21 variants, and protein modeling and dynamics can be helpful in determining pathogenicity. The current study should be helpful when counseling families with a RAD21 variation.

Translational studies of intravenous and intracerebroventricular routes of administration for CNS cellular biodistribution for BMN 250, an enzyme replacement therapy for the treatment of Sanfilippo type B - Anita Grover; Danielle Crippen-Harmon; Lacey Nave; Jon Vincelette; Jill C. M. Wait; Andrew C. Melton; Roger Lawrence; Jillian R. Brown; Katherine A. Webster; Bryan K. Yip; Brian Baridon; Catherine Vitelli; et al. (Drug Delivery and Translational Research, 2020)
BMN 250 is being developed as enzyme replacement therapy for Sanfilippo type B, a primarily neurological rare disease, in which patients have deficient lysosomal alpha- N -acetylglucosaminidase (NAGLU) enzyme activity. BMN 250 is taken up in target cells by the cation-independent mannose 6-phosphate receptor (CI-MPR, insulin-like growth factor 2 receptor), which then facilitates transit to the lysosome. BMN 250 is dosed directly into the central nervous system via the intracerebroventricular (ICV) route, and the objective of this work was to compare systemic intravenous (IV) and ICV delivery of BMN 250 to confirm the value of ICV dosing. We first assess the ability of enzyme to cross a potentially compromised blood–brain barrier in the Naglu −/− mouse model and then assess the potential for CI-MPR to be employed for receptor-mediated transport across the blood–brain barrier. In wild-type and Naglu −/− mice, CI-MPR expression in brain vasculature is high during the neonatal period but virtually absent by adolescence. In contrast, CI-MPR remains expressed through adolescence in non-affected non-human primate and human brain vasculature. Combined results from IV administration of BMN 250 in Naglu −/− mice and IV and ICV administration in healthy juvenile non-human primates suggest a limitation to therapeutic benefit from IV administration because enzyme distribution is restricted to brain vascular endothelial cells: enzyme does not reach target neuronal cells following IV administration, and pharmacological response following IV administration is likely restricted to clearance of substrate in endothelial cells. In contrast, ICV administration enables central nervous system enzyme replacement with biodistribution to target cells.

Comparison of bonobo and chimpanzee brain microstructure reveals differences in socio-emotional circuits - Habon A. Issa; Nicky Staes; Sophia Diggs-Galligan; Cheryl D. Stimpson; Annette Gendron-Fitzpatrick; Jared P. Taglialatela; Patrick R. Hof; William D. Hopkins; Chet C. Sherwood (Brain Structure and Function, 2019)

Restoration of wetlands: successes and failures on scalds comprising an iron oxide clogged layer with areas of acid sulfate soils - W. K. Gardner; R.W. Fitzpatrick; C. A. Hindhaugh (Plant and Soil, 2018)

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

How will climate novelty influence ecological forecasts? Using the Quaternary to assess future reliability - Matthew C. Fitzpatrick; Jessica L. Blois; John W. Williams; Diego Nieto‐Lugilde; Kaitlin C. Maguire; David J. Lorenz (Global Change Biology, 2018)
Future climates are projected to be highly novel relative to recent climates. Climate novelty challenges models that correlate ecological patterns to climate variables and then use these relationships to forecast ecological responses to future climate change. Here, we quantify the magnitude and ecological significance of future climate novelty by comparing it to novel climates over the past 21,000 years in North America. We then use relationships between model performance and climate novelty derived from the fossil pollen record from eastern North America to estimate the expected decrease in predictive skill of ecological forecasting models as future climate novelty increases. We show that, in the high emissions scenario (RCP 8.5) and by late 21st century, future climate novelty is similar to or higher than peak levels of climate novelty over the last 21,000 years. The accuracy of ecological forecasting models is projected to decline steadily over the coming decades in response to increasing climate novelty, although models that incorporate co‐occurrences among species may retain somewhat higher predictive skill. In addition to quantifying future climate novelty in the context of late Quaternary climate change, this work underscores the challenges of making reliable forecasts to an increasingly novel future, while highlighting the need to assess potential avenues for improvement, such as increased reliance on geological analogs for future novel climates and improving existing models by pooling data through time and incorporating assemblage‐level information.

Conserving rare species can have high opportunity costs for common species - Thomas M. Neeson; Patrick J. Doran; Michael C. Ferris; Kimberly B. Fitzpatrick; Matthew Herbert; Mary Khoury; Allison T. Moody; Jared Ross; Eugene Yacobson; Peter B. McIntyre (Global Change Biology, 2018)
Conservation practitioners face difficult choices in apportioning limited resources between rare species (to ensure their existence) and common species (to ensure their abundance and ecosystem contributions). We quantified the opportunity costs of conserving rare species of migratory fishes in the context of removing dams and retrofitting road culverts across 1,883 tributaries of the North American Great Lakes. Our optimization models show that maximizing total habitat gains across species can be very efficient in terms of benefits achieved per dollar spent, but disproportionately benefits common species. Conservation approaches that target rare species, or that ensure some benefits for every species (i.e., complementarity) enable strategic allocation of resources among species but reduce aggregate habitat gains. Thus, small habitat gains for the rarest species necessarily come at the expense of more than 20 times as much habitat for common ones. These opportunity costs are likely to occur in many ecosystems because range limits and conservation costs often vary widely among species. Given that common species worldwide are declining more rapidly than rare ones within major taxa, our findings provide incentive for triage among multiple worthy conservation targets.

An experimental test of alternative population augmentation scenarios - John A. Kronenberger; Jill C. Gerberich; Sarah W. Fitzpatrick; E. Dale Broder; Lisa M. Angeloni; W. Chris Funk (Conservation Biology, 2018)
Human land use is fragmenting habitats worldwide and inhibiting dispersal among previously connected populations of organisms, often leading to inbreeding depression and reduced evolutionary potential in the face of rapid environmental change. To combat this augmentation of isolated populations with immigrants is sometimes used to facilitate demographic and genetic rescue. Augmentation with immigrants that are genetically and adaptively similar to the target population effectively increases population fitness, but if immigrants are very genetically or adaptively divergent, augmentation can lead to outbreeding depression. Despite well‐cited guidelines for the best practice selection of immigrant sources, often only highly divergent populations remain, and experimental tests of these riskier augmentation scenarios are essentially nonexistent. We conducted a mesocosm experiment with Trinidadian guppies (Poecilia reticulata) to test the multigenerational demographic and genetic effects of augmenting 2 target populations with 3 types of divergent immigrants. We found no evidence of demographic rescue, but we did observe genetic rescue in one population. Divergent immigrant treatments tended to maintain greater genetic diversity, abundance, and hybrid fitness than controls that received immigrants from the source used to seed the mesocosms. In the second population, divergent immigrants had a slightly negative effect in one treatment, and the benefits of augmentation were less apparent overall, likely because this population started with higher genetic diversity and a lower reproductive rate that limited genetic admixture. Our results add to a growing consensus that gene flow can increase population fitness even when immigrants are more highly divergent and may help reduce uncertainty about the use of augmentation in conservation.

The interplay of climate and land use change affects the distribution of EU bumblebees - Leon Marshall; Jacobus C. Biesmeijer; Pierre Rasmont; Nicolas J. Vereecken; Libor Dvorak; Una Fitzpatrick; Frédéric Francis; Johann Neumayer; Frode Ødegaard; Juho P. T. Paukkunen; Tadeusz Pawlikowski; Menno Reemer; et al. (Global Change Biology, 2018)
Bumblebees in Europe have been in steady decline since the 1900s. This decline is expected to continue with climate change as the main driver. However, at the local scale, land use and land cover ( LULC ) change strongly affects the occurrence of bumblebees. At present, LULC change is rarely included in models of future distributions of species. This study's objective is to compare the roles of dynamic LULC change and climate change on the projected distribution patterns of 48 European bumblebee species for three change scenarios until 2100 at the scales of Europe, and Belgium, Netherlands and Luxembourg ( BENELUX ). We compared three types of models: (1) only climate covariates, (2) climate and static LULC covariates and (3) climate and dynamic LULC covariates. The climate and LULC change scenarios used in the models include, extreme growth applied strategy ( GRAS ), business as might be usual and sustainable European development goals. We analysed model performance, range gain/loss and the shift in range limits for all bumblebees. Overall, model performance improved with the introduction of LULC covariates. Dynamic models projected less range loss and gain than climate‐only projections, and greater range loss and gain than static models. Overall, there is considerable variation in species responses and effects were most pronounced at the BENELUX scale. The majority of species were predicted to lose considerable range, particularly under the extreme growth scenario ( GRAS ; overall mean: 64% ± 34). Model simulations project a number of local extinctions and considerable range loss at the BENELUX scale (overall mean: 56% ± 39). Therefore, we recommend species‐specific modelling to understand how LULC and climate interact in future modelling. The efficacy of dynamic LULC change should improve with higher thematic and spatial resolution. Nevertheless, current broad scale representations of change in major land use classes impact modelled future distribution patterns.

Golden Eagle fatalities and the continental‐scale consequences of local wind‐energy generation - Todd E. Katzner; David M. Nelson; Melissa A. Braham; Jacqueline M. Doyle; Nadia B. Fernandez; Adam E. Duerr; Peter H. Bloom; Matthew C. Fitzpatrick; Tricia A. Miller; Renee C. E. Culver; Loan Braswell; J. Andrew DeWoody (Conservation Biology, 2017)
Renewable energy production is expanding rapidly despite mostly unknown environmental effects on wildlife and habitats. We used genetic and stable isotope data collected from Golden Eagles (Aquila chrysaetos) killed at the Altamont Pass Wind Resource Area (APWRA) in California in demographic models to test hypotheses about the geographic extent and demographic consequences of fatalities caused by renewable energy facilities. Geospatial analyses of δ 2 H values obtained from feathers showed that ≥25% of these APWRA‐killed eagles were recent immigrants to the population, most from long distances away (>100 km). Data from nuclear genes indicated this subset of immigrant eagles was genetically similar to birds identified as locals from the δ 2 H data. Demographic models implied that in the face of this mortality, the apparent stability of the local Golden Eagle population was maintained by continental‐scale immigration. These analyses demonstrate that ecosystem management decisions concerning the effects of local‐scale renewable energy can have continental‐scale consequences.

Theory of Visual Attention (TVA) applied to mice in the 5-choice serial reaction time task - C. M. Fitzpatrick; M. Caballero-Puntiverio; U. Gether; T. Habekost; C. Bundesen; S. Vangkilde; D. P. D. Woldbye; J. T. Andreasen; A. Petersen (Psychopharmacology, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Adaptive divergence despite strong genetic drift: genomic analysis of the evolutionary mechanisms causing genetic differentiation in the island fox ( Urocyon littoralis ) - W. Chris Funk; Robert E. Lovich; Paul A. Hohenlohe; Courtney A. Hofman; Scott A. Morrison; T. Scott Sillett; Cameron K. Ghalambor; Jesus E. Maldonado; Torben C. Rick; Mitch D. Day; Nicholas R. Polato; Sarah W. Fitzpatrick; et al. (Molecular Ecology, 2016)
The evolutionary mechanisms generating the tremendous biodiversity of islands have long fascinated evolutionary biologists. Genetic drift and divergent selection are predicted to be strong on islands and both could drive population divergence and speciation. Alternatively, strong genetic drift may preclude adaptation. We conducted a genomic analysis to test the roles of genetic drift and divergent selection in causing genetic differentiation among populations of the island fox ( Urocyon littoralis ). This species consists of six subspecies, each of which occupies a different California Channel Island. Analysis of 5293 SNP loci generated using Restriction‐site Associated DNA ( RAD ) sequencing found support for genetic drift as the dominant evolutionary mechanism driving population divergence among island fox populations. In particular, populations had exceptionally low genetic variation, small N e (range = 2.1–89.7; median = 19.4), and significant genetic signatures of bottlenecks. Moreover, islands with the lowest genetic variation (and, by inference, the strongest historical genetic drift) were most genetically differentiated from mainland grey foxes, and vice versa, indicating genetic drift drives genome‐wide divergence. Nonetheless, outlier tests identified 3.6–6.6% of loci as high F ST outliers, suggesting that despite strong genetic drift, divergent selection contributes to population divergence. Patterns of similarity among populations based on high F ST outliers mirrored patterns based on morphology, providing additional evidence that outliers reflect adaptive divergence. Extremely low genetic variation and small N e in some island fox populations, particularly on San Nicolas Island, suggest that they may be vulnerable to fixation of deleterious alleles, decreased fitness and reduced adaptive potential.

Close agreement between pollen‐based and forest inventory‐based models of vegetation turnover - Diego Nieto‐Lugilde; Kaitlin C. Maguire; Jessica L. Blois; John W. Williams; Matthew C. Fitzpatrick (Global Ecology and Biogeography, 2015)
Aim Fossil records are being increasingly used to help understand the consequences of climate change for biodiversity. Pollen records from the late Q uaternary are among the most commonly used fossil data, but pollen‐based inferences of biodiversity can potentially be confounded by spatial and taxonomic uncertainties and the influence of non‐climatic abiotic factors such as soils on vegetation–climate relationships. Using paired pollen and vegetation inventories, we assess the fidelity of pollen‐based estimates of compositional turnover of vegetation along environmental gradients given various sources of uncertainty. Location E astern U nited S tates. Methods We used modern pollen records and forest composition data from F orest I nventory and A nalysis ( FIA ) plots to fit generalized dissimilarity models. To address how uncertainties in pollen records affect estimates of turnover, we coarsened the vegetation data spatially from individual plots to 10‐ and 30‐arcmin resolution and taxonomically from species to genus. To determine whether soil properties influenced turnover, we used deviance partitioning between models including climate or soil variables versus models with a combination of both. Results Pollen‐based estimates of turnover were highly correlated with those based on FIA data, but tended to be lower, mainly due to differences in taxonomic resolution and secondarily to differences in spatial resolution. Neither spatial nor taxonomic uncertainty substantially reduced the correlation between pollen‐ and FIA ‐based estimates of turnover. FIA data best matched pollen records when they were aggregated to genus and 30‐arcmin resolution. Vegetation–climate relationships were similar across datasets, although models sometimes differed. The influence of soil variables was negligible compared with climate variables and did not improve model fit. Pollen thresholds did not greatly affect the form and strength of pollen–vegetation relationships. Main conclusions Pollen can act as a robust proxy for vegetation turnover, thereby supporting the use of pollen‐based estimates of turnover to predict temporal changes in vegetation.

Ecological genomics meets community‐level modelling of biodiversity: mapping the genomic landscape of current and future environmental adaptation - Matthew C. Fitzpatrick; Stephen R. Keller (Ecology Letters, 2015)
Local adaptation is a central feature of most species occupying spatially heterogeneous environments, and may factor critically in responses to environmental change. However, most efforts to model the response of species to climate change ignore intraspecific variation due to local adaptation. Here, we present a new perspective on spatial modelling of organism–environment relationships that combines genomic data and community‐level modelling to develop scenarios regarding the geographic distribution of genomic variation in response to environmental change. Rather than modelling species within communities, we use these techniques to model large numbers of loci across genomes. Using balsam poplar ( Populus balsamifera ) as a case study, we demonstrate how our framework can accommodate nonlinear responses of loci to environmental gradients. We identify a threshold response to temperature in the circadian clock gene GIGANTEA ‐5 ( GI 5 ), suggesting that this gene has experienced strong local adaptation to temperature. We also demonstrate how these methods can map ecological adaptation from genomic data, including the identification of predicted differences in the genetic composition of populations under current and future climates. Community‐level modelling of genomic variation represents an important advance in landscape genomics and spatial modelling of biodiversity that moves beyond species‐level assessments of climate change vulnerability.

Locally adapted traits maintained in the face of high gene flow - S. W. Fitzpatrick; J. C. Gerberich; J. A. Kronenberger; L. M. Angeloni; W. C. Funk (Ecology Letters, 2015)
Gene flow between phenotypically divergent populations can disrupt local adaptation or, alternatively, may stimulate adaptive evolution by increasing genetic variation. We capitalised on historical Trinidadian guppy transplant experiments to test the phenotypic effects of increased gene flow caused by replicated introductions of adaptively divergent guppies, which were translocated from high‐ to low‐predation environments. We sampled two native populations prior to the onset of gene flow, six historic introduction sites, introduction sources and multiple downstream points in each basin. Extensive gene flow from introductions occurred in all streams, yet adaptive phenotypic divergence across a gradient in predation level was maintained. Descendants of guppies from a high‐predation source site showed high phenotypic similarity with native low‐predation guppies in as few as ~12 generations after gene flow, likely through a combination of adaptive evolution and phenotypic plasticity. Our results demonstrate that locally adapted phenotypes can be maintained despite extensive gene flow from divergent populations.

Aspirated bile: a major host trigger modulating respiratory pathogen colonisation in cystic fibrosis patients - F. J. Reen; D. F. Woods; M. J. Mooij; M. N. Chróinín; D. Mullane; L. Zhou; J. Quille; D. Fitzpatrick; J. D. Glennon; G. P. McGlacken; C. Adams; F. O’Gara (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Thermal tolerance affects mutualist attendance in an ant–plant protection mutualism - Ginny Fitzpatrick; Michele C. Lanan; Judith L. Bronstein (Oecologia, 2014)

A Community-based Collaborative Approach to Improve Breast Cancer Screening in Underserved African American Women - Rachel Karcher; Dawn C. Fitzpatrick; Dawn J. Leonard; Scott Weber (Journal of Cancer Education, 2014)

Water availability strongly impacts population genetic patterns of an imperiled Great Plains endemic fish - S. W. Fitzpatrick; H. Crockett; W. C. Funk (Conservation Genetics, 2014)

Sources of variance in a female fertility signal: exaggerated estrous swellings in a natural population of baboons - Courtney L. Fitzpatrick; Jeanne Altmann; Susan C. Alberts (Behavioral Ecology and Sociobiology, 2014)

Modeling the spread of invasive species using dynamic network models - Joseph R. Ferrari; Evan L. Preisser; Matthew C. Fitzpatrick (Biological Invasions, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Isolation and characterization of eight polymorphic microsatellite loci for Natterer’s bat, Myotis nattereri (Vespertilionidae, Chiroptera) - David D. Scott; Seán Fitzpatrick; Deborah A. Bailie; Emma S. M. Boston; Mathieu G. Lundy; Daniel J. Buckley; Emma C. Teeling; W. Ian Montgomery; Paulo A. Prodöhl (Conservation Genetics Resources, 2013)

Clinical and mutation data in 12 patients with the clinical diagnosis of Nager syndrome - J. C. Czeschik; C. Voigt; Y. Alanay; B. Albrecht; S. Avci; D. FitzPatrick; D. R. Goudie; U. Hehr; A. J. Hoogeboom; H. Kayserili; P. O. Simsek-Kiper; L. Klein-Hitpass; et al. (Human Genetics, 2013)

Doomed before they are described? The need for conservation assessments of cryptic species complexes using an amblyopsid cavefish (Amblyopsidae: Typhlichthys) as a case study - Matthew L. Niemiller; Gary O. Graening; Dante B. Fenolio; James C. Godwin; James R. Cooley; William D. Pearson; Benjamin M. Fitzpatrick; Thomas J. Near (Biodiversity and Conservation, 2013)

Response of diurnal and nocturnal coral reef fish to protection from fishing: an assessment using baited remote underwater video - E. S. Harvey; S. R. Dorman; C. Fitzpatrick; S. J. Newman; D. L. McLean (Coral Reefs, 2012)

Symbiodinium diversity in the soft coral Heteroxenia sp. and its nudibranch predator Phyllodesmium lizardensis - S. K. FitzPatrick; K. L. Liberatore; J. R. Garcia; I. Burghardt; D. R. Colman; S. A. Moquin; C. D. Takacs-Vesbach; U. L. Shepherd (Coral Reefs, 2012)

Archaeology and coastal conservation - Torben C. Rick; Scott M. Fitzpatrick (Journal of Coastal Conservation, 2012)

Measuring ecological niche overlap from occurrence and spatial environmental data - Olivier Broennimann; Matthew C. Fitzpatrick; Peter B. Pearman; Blaise Petitpierre; Loïc Pellissier; Nigel G. Yoccoz; Wilfried Thuiller; Marie‐Josée Fortin; Christophe Randin; Niklaus E. Zimmermann; Catherine H. Graham; Antoine Guisan (Global Ecology and Biogeography, 2012)
Aim Concerns over how global change will influence species distributions, in conjunction with increased emphasis on understanding niche dynamics in evolutionary and community contexts, highlight the growing need for robust methods to quantify niche differences between or within taxa. We propose a statistical framework to describe and compare environmental niches from occurrence and spatial environmental data. Location Europe, North America and South America. Methods The framework applies kernel smoothers to densities of species occurrence in gridded environmental space to calculate metrics of niche overlap and test hypotheses regarding niche conservatism. We use this framework and simulated species with pre‐defined distributions and amounts of niche overlap to evaluate several ordination and species distribution modelling techniques for quantifying niche overlap. We illustrate the approach with data on two well‐studied invasive species. Results We show that niche overlap can be accurately detected with the framework when variables driving the distributions are known. The method is robust to known and previously undocumented biases related to the dependence of species occurrences on the frequency of environmental conditions that occur across geographical space. The use of a kernel smoother makes the process of moving from geographical space to multivariate environmental space independent of both sampling effort and arbitrary choice of resolution in environmental space. However, the use of ordination and species distribution model techniques for selecting, combining and weighting variables on which niche overlap is calculated provide contrasting results. Main conclusions The framework meets the increasing need for robust methods to quantify niche differences. It is appropriate for studying niche differences between species, subspecies or intra‐specific lineages that differ in their geographical distributions. Alternatively, it can be used to measure the degree to which the environmental niche of a species or intra‐specific lineage has changed over time.

The human semicircular canal model of galvanic vestibular stimulation - Brian L. Day; Elijane Ramsay; Miriam S. Welgampola; Richard C. Fitzpatrick (Experimental Brain Research, 2011)

Ecological boundary detection using Bayesian areal wombling - Matthew C. Fitzpatrick; Evan L. Preisser; Adam Porter; Joseph Elkinton; Lance A. Waller; Bradley P. Carlin; Aaron M. Ellison (Ecology, 2010)
The study of ecological boundaries and their dynamics is of fundamental importance to much of ecology, biogeography, and evolution. Over the past two decades, boundary analysis (of which wombling is a subfield) has received considerable research attention, resulting in multiple approaches for the quantification of ecological boundaries. Nonetheless, few methods have been developed that can simultaneously (1) analyze spatially homogenized data sets (i.e., areal data in the form of polygons rather than point‐reference data); (2) account for spatial structure in these data and uncertainty associated with them; and (3) objectively assign probabilities to boundaries once detected. Here we describe the application of a Bayesian hierarchical framework for boundary detection developed in public health, which addresses these issues but which has seen limited application in ecology. As examples, we analyze simulated spread data and the historic pattern of spread of an invasive species, the hemlock woolly adelgid ( Adelges tsugae ), using county‐level summaries of the year of first reported infestation and several covariates potentially important to influencing the observed spread dynamics. Bayesian areal wombling is a promising approach for analyzing ecological boundaries and dynamics related to changes in the distributions of native and invasive species.

Gene trees, species and species trees in the Ctenosaura palearis clade - Stesha A. Pasachnik; Arthur C. Echternacht; Benjamin M. Fitzpatrick (Conservation Genetics, 2010)

Geography disentangles introgression from ancestral polymorphism in Lake Malawi cichlids - MERYL C. MIMS; C. DARRIN HULSEY; BENJAMIN M. FITZPATRICK; J. TODD STREELMAN (Molecular Ecology, 2010)
Phenotypically diverse Lake Malawi cichlids exhibit similar genomes. The extensive sharing of genetic polymorphism among forms has both intrigued and frustrated biologists trying to understand the nature of diversity in this and other rapidly evolving systems. Shared polymorphism might result from hybridization and/or the retention of ancestrally polymorphic alleles. To examine these alternatives, we used new genomic tools to characterize genetic differentiation in widespread, geographically structured populations of Labeotropheus fuelleborni and Metriaclima zebra . These phenotypically distinct species share mitochondrial DNA (mtDNA) haplotypes and show greater mtDNA differentiation among localities than between species. However, Bayesian analysis of nuclear single nucleotide polymorphism (SNP) data revealed two distinct genetic clusters corresponding perfectly to morphologically diagnosed L. fuelleborni and M. zebra . This result is a function of the resolving power of the multi‐locus dataset, not a conflict between nuclear and mitochondrial partitions. Locus‐by‐locus analysis showed that mtDNA differentiation between species ( F CT ) was nearly identical to the median single‐locus SNP F CT . Finally, we asked whether there is evidence for gene flow at sites of co‐occurrence. We used simulations to generate a null distribution for the level of differentiation between co‐occurring populations of L. fuelleborni and M. zebra expected if there was no hybridization. The null hypothesis was rejected for the SNP data; populations that co‐occur at rock reef sites were slightly more similar than expected by chance, suggesting recent gene flow. The coupling of numerous independent markers with extensive geographic sampling and simulations utilized here provides a framework for assessing the prevalence of gene flow in recently diverged species.

Gene flow between an endangered endemic iguana, and its wide spread relative, on the island of Utila, Honduras: when is hybridization a threat? - Stesha A. Pasachnik; Benjamin M. Fitzpatrick; Thomas J. Near; Arthur C. Echternacht (Conservation Genetics, 2009)

Dispersal traits linked to range size through range location, not dispersal ability, in Western Australian angiosperms - Aaron D. Gove; Matthew C. Fitzpatrick; Jonathan D. Majer; Robert R. Dunn (Global Ecology and Biogeography, 2009)
Aim We examine the relative importance of seed dispersal mode in determining the range size and range placement in 524 species from six focal plant families (Agavaceae, Euphorbiaceae, Malvacaeae, Sapindaceae, Proteaceae and Fabaceae ( Acacia )). Location Western Australia. Methods Taxa were categorized by dispersal mode and life‐form and their distributions modelled using maxent . Geographical range size was compared amongst dispersal mode, life‐form and biome using phylogenetically independent contrasts. Geographical range placement was considered in a similar manner. Results Range size did not vary with dispersal mode (ant versus wind and vertebrate dispersal) or life‐form, and instead varied primarily as a function of the biogeographical region in which a species was found. Range placement, however, did vary among dispersal modes, with the consequence that diversity of wind‐ and ant‐dispersed plants increased with latitude while the diversity of vertebrate‐dispersed plants was more evenly distributed. Main conclusions For the taxa studied, range sizes were a function of the biogeographical region in which species were found. Although differences in range size may exist among species differing in dispersal modes, they are likely to be far smaller than differences among species from different biogeographical regions. The trait most likely to affect species geographical range size, and hence rarity and risks associated with other threats, may simply be the geographical region in which that species has evolved.

Geomorphology of a dryland fluvial system: the Lower Balonne River, southern Queensland - A. L. Kernich; C. F. Pain; J. D. A. Clarke; A. D. Fitzpatrick (Australian Journal of Earth Sciences, 2009)

The projection of species distribution models and the problem of non-analog climate - Matthew C. Fitzpatrick; William W. Hargrove (Biodiversity and Conservation, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Data sets matter, but so do evolution and ecology - Matthew C. Fitzpatrick; Robert R. Dunn; Nathan J. Sanders (Global Ecology and Biogeography, 2008)

Climate change, plant migration, and range collapse in a global biodiversity hotspot: the Banksia (Proteaceae) of Western Australia - MATTHEW C. FITZPATRICK; AARON D. GOVE; NATHAN J. SANDERS; ROBERT R. DUNN (Global Change Biology, 2008)
Climate change has already altered global patterns of biodiversity by modifying the geographic distributions of species. Forecasts based on bioclimatic envelop modeling of distributions of species suggests greater impacts can be expected in the future, but such projections are contingent on assumptions regarding future climate and migration rates of species. Here, we present a first assessment of the potential impact of climate change on a global biodiversity hotspot in southwestern Western Australia. Across three representative scenarios of future climate change, we simulated migration of 100 Banksia (Proteaceae) species at a rate of 5 km decade −1 and compared projected impacts with those under the commonly applied, but acknowledged as inadequate, assumptions of ‘full‐’ and ‘no‐migration.’ Across all climate × migration scenarios, 66% of species were projected to decline, whereas only 6% were projected to expand or remain stable. Between 5% and 25% of species were projected to suffer range losses of 100% by 2080, depending mainly on climate scenario. Species losses were driven primarily by changes in current precipitation regimes, with the greatest losses of species projected to occur in a transition zone between wet coastal areas and interior arid regions and which is projected to become more arid in the future. Because the ranges of most species tended to collapse in all climate scenarios, we found that climate change impacts to flora of southwestern Western Australia may be large, even under optimistic assumptions regarding migration abilities. Taken together, our results suggest that the future of biodiversity in southwestern Western Australia may lie largely in the degree to which this hotspot experiences increased drought and in the ability of species to tolerate such decreases in precipitation. More broadly, our study is among a growing number of theoretical studies suggesting the impacts of future climate change on global biodiversity may be considerable.

Congruent population structure inferred from dispersal behaviour and intensive genetic surveys of the threatened Florida scrub‐jay ( Aphelocoma cœrulescens ) - A. COULON; J. W. FITZPATRICK; R. BOWMAN; B. M. STITH; C. A. MAKAREWICH; L. M. STENZLER; I. J. LOVETTE (Molecular Ecology, 2008)
The delimitation of populations, defined as groups of individuals linked by gene flow, is possible by the analysis of genetic markers and also by spatial models based on dispersal probabilities across a landscape. We combined these two complimentary methods to define the spatial pattern of genetic structure among remaining populations of the threatened Florida scrub‐jay, a species for which dispersal ability is unusually well‐characterized. The range‐wide population was intensively censused in the 1990s, and a metapopulation model defined population boundaries based on predicted dispersal‐mediated demographic connectivity. We subjected genotypes from more than 1000 individual jays screened at 20 microsatellite loci to two Bayesian clustering methods. We describe a consensus method for identifying common features across many replicated clustering runs. Ten genetically differentiated groups exist across the present‐day range of the Florida scrub‐jay. These groups are largely consistent with the dispersal‐defined metapopulations, which assume very limited dispersal ability. Some genetic groups comprise more than one metapopulation, likely because these genetically similar metapopulations were sundered only recently by habitat alteration. The combined reconstructions of population structure based on genetics and dispersal‐mediated demographic connectivity provide a robust depiction of the current genetic and demographic organization of this species, reflecting past and present levels of dispersal among occupied habitat patches. The differentiation of populations into 10 genetic groups adds urgency to management efforts aimed at preserving what remains of genetic variation in this dwindling species, by maintaining viable populations of all genetically differentiated and geographically isolated populations.

Temperature, but not productivity or geometry, predicts elevational diversity gradients in ants across spatial grains - Nathan J. Sanders; Jean‐Philippe Lessard; Matthew C. Fitzpatrick; Robert R. Dunn (Global Ecology and Biogeography, 2007)
Aim This research aims to understand the factors that shape elevational diversity gradients and how those factors vary with spatial grain. Specifically, we test the predictions of the species–productivity hypothesis, species–temperature hypothesis, the metabolic theory of ecology and the mid‐domain effects null model. We also examine how the effects of productivity and temperature on richness depend on spatial grain. Location Deciduous forests along an elevational gradient in Great Smoky Mountains National Park, USA. Methods We sampled 22 leaf litter ant assemblages at three spatial grains, from 1‐m 2 quadrats to 50 × 50 m plots using Winkler samplers. Results Across spatial grains, warmer sites had more species than did cooler sites, and primary productivity did not predict ant species richness. We found some support for the predictions of the metabolic theory of ecology, but no support for the mid‐domain effects null model. Thus, our data are best explained by some version of a species–temperature hypothesis. Main conclusions Our results suggest that temperature indirectly affects ant species diversity across spatial grains, perhaps by limiting access to resources. Warmer sites support more species because they support more individuals, thereby reducing the probability of local extinction. Many of our results from this elevational gradient agree with studies at more global scales, suggesting that some mechanisms shaping ant diversity gradients are common across scales.

The biogeography of prediction error: why does the introduced range of the fire ant over‐predict its native range? - Matthew C. Fitzpatrick; Jake F. Weltzin; Nathan J. Sanders; Robert R. Dunn (Global Ecology and Biogeography, 2007)
Aim The use of species distribution models (SDMs) to predict biological invasions is a rapidly developing area of ecology. However, most studies investigating SDMs typically ignore prediction errors and instead focus on regions where native distributions correctly predict invaded ranges. We investigated the ecological significance of prediction errors using reciprocal comparisons between the predicted invaded and native range of the red imported fire ant ( Solenopsis invicta ) (hereafter called the fire ant). We questioned whether fire ants occupy similar environments in their native and introduced range, how the environments that fire ants occupy in their introduced range changed through time relative to their native range, and where fire ant propagules are likely to have originated. Location We developed models for South America and the conterminous United States (US) of America. Methods We developed models using the Genetic Algorithm for Rule‐set Prediction (GARP) and 12 environmental layers. Occurrence data from the native range in South America were used to predict the introduced range in the US and vice versa. Further, time‐series data recording the invasion of fire ants in the US were used to predict the native range. Results Native range occurrences under‐predicted the invasive potential of fire ants, whereas occurrence data from the US over‐predicted the southern boundary of the native range. Secondly, introduced fire ants initially established in environments similar to those in their native range, but subsequently invaded harsher environments. Time‐series data suggest that fire ant propagules originated near the southern limit of their native range. Conclusions Our findings suggest that fire ants from a peripheral native population established in an environment similar to their native environment, and then ultimately expanded into environments in which they are not found in their native range. We argue that reciprocal comparisons between predicted native and invaded ranges will facilitate a better understanding of the biogeography of invasive and native species and of the role of SDMs in predicting future distributions.

The biogeography of prediction error: why does the introduced range of the fire ant over-predict its native range? - Matthew C. Fitzpatrick; Jake F. Weltzin; Nathan J. Sanders; Robert R. Dunn (Global Ecology and Biogeography, 2006)

In Ovo Exposure to a Triazine Herbicide: Effects of Atrazine on Circulating Reproductive Hormones and Gonadal Histology in Young Japanese Quail - K. W. Wilhelms; K. F. Fitzpatrick; C. G. Scanes; L. L. Anderson (Archives of Environmental Contamination and Toxicology, 2006)

Novel titanocene anti-cancer drugs and their effect on apoptosis and the apoptotic pathway in prostate cancer cells - K. O'Connor; C. Gill; M. Tacke; F.-J. K. Rehmann; K. Strohfeldt; N. Sweeney; J. M. Fitzpatrick; R. W. G. Watson (Apoptosis, 2006)

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

Gonad Organochlorine Concentrations and Plasma Steroid Levels in White Sturgeon ( Acipenser transmontanus ) from the Columbia River, USA - E. P. Foster; M. S. Fitzpatrick; G. W. Feist; C. B. Schreck; J. Yates (Bulletin of Environmental Contamination and Toxicology, 2001)

Passive tactile sensory input improves stability during standing - Mark W. Rogers; Daniel L. Wardman; Stephen R. Lord; Richard C. Fitzpatrick (Experimental Brain Research, 2001)

Lack of pharmacokinetic interaction between ropinirole and theophylline in patients with Parkinson's disease - C. Thalamas; A. Taylor; C. Brefel-Courbon; S. Eagle; K. Fitzpatrick; O. Rascol (European Journal of Clinical Pharmacology, 1999)

In Vitro Earthworm Lumbricus terrestris Coelomocyte Assay for Use in Terrestrial Toxicity Identification Evaluation - S. W. Burch; L. C. Fitzpatrick; A. J. Goven; B. J. Venables; M. A. Giggleman (Bulletin of Environmental Contamination and Toxicology, 1999)

Wound Healing in Earthworms Lumbricus terrestris: A Cellular-Based Biomarker for Assessing Sublethal Chemical Toxicity - M. A. Cikutovic; L. C. Fitzpatrick; A. J. Goven; B. J. Venables; M. A. Giggleman; E. L. Cooper (Bulletin of Environmental Contamination and Toxicology, 1999)

Continued studies of the relationship of specific gravity to total solids of potatoes - T. J. Fitzpatrick; W. L. Porter; G. V. C. Houghland (American Journal of Potato Research, 1969)